Yttrium-90 microsphere radioembolization in unresectable intrahepatic cholangiocarcinoma. (June 2017) - Mosconi, Cristina; Cappelli, Alberta; Ascanio, Salvatore; Pettinari, Irene; Modestino, Francesco; Renzulli, Matteo; Galaverni, Maria Cristina; Cucchetti, Alessandro; Gramenzi, Annagiulia; Pettinato, Cinzia; Golfieri, Rita
Intrahepatic cholangiocarcinoma is increasing in frequency worldwide, but radical surgical treatment is practicable in 30–40% of cases. The median survival without therapy is about 8 months, increased to 12 months in combination with systemic chemotherapy. Therefore, locoregional therapies, such as, radiofrequency ablation or transarterial chemoembolization have been employed. Radioembolization with yttrium-90 microspheres ( 90 Y-TARE) is a novel intrarterial treatment which could be included in the armamentarium of treatment options, having shown higher median survival (up to 22 months) and low complication rates. Evidence-based algorithms for staging and allocation to treatment should be defined in the future, after robust results obtained through randomized controlled trials, thus establishing the exact role and timing of 90 Y-TARE in the treatment protocol of unresectable intrahepatic cholangiocarcinoma.